2017
DOI: 10.1371/journal.pone.0185936
|View full text |Cite
|
Sign up to set email alerts
|

Is two better than one? Muscle vibration plus robotic rehabilitation to improve upper limb spasticity and function: A pilot randomized controlled trial

Abstract: Even though robotic rehabilitation is very useful to improve motor function, there is no conclusive evidence on its role in reducing post-stroke spasticity. Focal muscle vibration (MV) is instead very useful to reduce segmental spasticity, with a consequent positive effect on motor function. Therefore, it could be possible to strengthen the effects of robotic rehabilitation by coupling MV. To this end, we designed a pilot randomized controlled trial (Clinical Trial NCT03110718) that included twenty patients su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 93 publications
0
51
1
9
Order By: Relevance
“…In the past few years, more effort has been paid to studying the effects of focal vibration (FV) at a high frequency (50∼120 Hz) and with a low amplitude on the rehabilitation of neurological diseases, such as stroke, spinal cord injury, multiple sclerosis, and cerebral palsy [1]. As for patients with stroke, FV can improve various abilities and functionalities, including walking [2], postural sway and gait ability [3], motor performances of reaching movement [4], stability of the proximal arm [5], and reducing spasticity [6, 7]. As for patients with spinal cord injury, FV reduced spasticity [1] and elicited stepping movements [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, more effort has been paid to studying the effects of focal vibration (FV) at a high frequency (50∼120 Hz) and with a low amplitude on the rehabilitation of neurological diseases, such as stroke, spinal cord injury, multiple sclerosis, and cerebral palsy [1]. As for patients with stroke, FV can improve various abilities and functionalities, including walking [2], postural sway and gait ability [3], motor performances of reaching movement [4], stability of the proximal arm [5], and reducing spasticity [6, 7]. As for patients with spinal cord injury, FV reduced spasticity [1] and elicited stepping movements [8].…”
Section: Introductionmentioning
confidence: 99%
“…Calabro et al reported that a similar approach applied to people with stroke can decrease spasticity and enhance movement kinematics [7]. They applied focal vibrations on the tendons whereas in this study FV was applied on the wrist joint flexor and extensor muscles of the forearm.…”
Section: Discussionmentioning
confidence: 97%
“…This could be of importance in spinal cord injury (SCI) rehabilitation to increase motor abilities of the residual movements. Calabro et al applied FV to a tendon and Casale et al to several arm and shoulder muscles during robotic-aided exercise for people with stroke and observed effectiveness in decreasing spasticity and improvement in volitional kinematic activities [7], [8]. On the other hand, Backus et al followed a similar approach for people with spinal cord injury with focal tendon vibration and reported little or no change in spasticity [9].…”
Section: Introductionmentioning
confidence: 99%
“…A useful tool to reduce segmental spasticity is represented by muscle vibration (MV), as suggested by reports on patients with stroke, multiple sclerosis, and cerebral palsy [15,16,17,18]. Vibrations have been already used to manage different pelvic floor dysfunctions due to diverse pathologies, but only employing whole body vibration (not addressing ED) or penile vibration used for ejaculation [19,20,21,22,23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…This may help to modify the corticospinal excitability, to favor intracortical inhibitory systems, and to induce better muscle synergy pattern by acting on the excitability of spinal motoneurons and interneurons. MV may directly act at the spinal level, reducing abnormalities of the spinal excitability (as the activation of primary Ia spindle afferents result in inhibition of the monosynaptic reflex) and restoring abnormal reciprocal and presynaptic inhibition mechanisms [15,16,17,18]. Altogether, these effects lead to a reduction in spasticity [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%